The Effect of BDNF Gene on Bipolar Disorder - Liu, Zichun; Zhang, Shuntong (Transactions on Materials, Biotechnology and Life Sciences, 2024)
BDNF (brain-derived neurotrophic factor) is a kind of neurotrophic protein, widely distributed in the brain and spinal cord. BDNF is engaged in regulating the growth and migration of neurons, and can promote the repair of damaged neurons. While disorders of BDNF expression can lead to mental diseases such as bipolar disorder. The main way in which the BDNF gene affects bipolar disorder is through BDNF’s interaction with TrkB receptors. In addition, BDNF also causes bipolar disorder by affecting the amygdala and hippocampus, promoting neuronal regeneration, and participating in synaptic plasticity. At present, there are still some questions in the field of bipolar disorder and BDNF gene research. The pathological mechanism of bipolar disorder is still unclear, and the clinical application of BDNF has many difficulties. This article reviews the BDNF gene influences the role and mechanism of bipolar disorder and the evidence that BDNF gene causes bipolar disorder, hoping to provide a new direction for the treatment of bipolar disorder.